The United States Urban Hierarchy: An Update - Griffith, Daniel A. (Frontiers in Sustainable Cities, 2022)
The sole well-recognized United States (US) urban hierarchy articulation essentially is outdated, even though selected recent work seeks to upgrade it. The primary goal of this paper is to update it in a definitive and comprehensive fashion. This paper describes the conceptual framework underlying such observed orderings, itemizes certain strengths and weaknesses of the existing articulation, and then posits a justifiable renovated US urban hierarchy. Next, recapped analyses expose both contiguity and urban hierarchy spatial autocorrelation components of the upper tiers of the 2020 US metropolitan area population rank size distribution. Noteworthy is that these descriptions entail positive-negative spatial autocorrelation mixtures. Inventoried output from the research efforts leading to this paper includes: a contemporary US urban hierarchy articulation that should prove serviceable for at least the next few decades; and, an apparatus providing a practical contribution for improving cultural, environmental, and social aspects of systems of cities through, for example, better cost containment and more efficient/effective delivery of urban public health services and utilization/consumption. The Earth's scientists need this category of tool to incorporate into methodology combating negative effects of globalization that materialize via spatial diffusion.